SEARCH OF THE STRESS INDUSED VENTRICULAR TACHICARDIA REASONS — THE METABOLIC THERAPY OPPORTUNITIES - T. V. Treshkur; A. A. Tatarinova; E. A. Ryngach (Архивъ внутренней медицины)
A clinical case of a 56-year-old man is presented in which only ventricular tachycardia without clinical and ECG criteria of myocardial ischemia is recorded on the exercise test. The ventricular tachycardia was the only reason for stopping the test. This clinical case demonstrates all the difficulties in determining the genesis of ventricular arrhythmias induced by exercise. The purpose of the work was to show all the difficulties in determining the genesis of exercise-induced ventricular arrhythmia. The literature references related to the exercise-induced ventricular arrhythmia differentiation is rather poor. It is only known that if a patient develops and progresses ventricular arrhythmia, a tredmill test is considered questionable. Exerciseinduced ventricular arrhythmias especially ventricular tachycardia, are the most dangerous. Therefore, additional diagnostic methods were used to reveal the main disease as the background of ventricular tachycardia. Results of pharmacological test with nitroglycerine were the indication of the ischemic origin of ventricular tachycardia. Coronary angiography did not reveal coronary artery stenoses. Positron emission tomography revealed coronary microcirculation disturbance after which a decision about metabolic therapy with Mexicor was made. The correct choice of the drug (Mеxisor) was confirmed by the results of control studies — improvement of metabolism and antiarrhythmic effect. The article concludes that the choice of the treatment exercise-induced ventricular arrhythmia in patients with stable coronary artery disease should be individual and pathogenetic.